Avaliação do impacto do desmatamento sobre o regime hidroclimático da bacia hidrográfica do rio Curuá-PA - Nascimento Filho, José Carlos Benicio do (2022)
In recent decades, the watersheds located in the Amazon region have been undergoing an intense process of deforestation and forest destruction. Measuring this deforestation and its impacts in the region is of paramount importance for efficient local environmental management. Therefore, the objective of this work was to evaluate the effect of deforestation on the main hydroclimatic components of the hydrographic basin of the Curuá River (BRC), located in the municipality of Altamira–Pará, in the Legal Amazon. In 198119811920, the best results by remote sensing showed results on monthly and annual time scales, with approximate values of RMSE of 45.8% (81.3 mm) and 21.2% (433.0 mm), respectively. For a more precise analysis of the water behavior of the basin, a study of its morphological characteristics was carried out from the digital model derived from the topographic mission of the shuttle radar, and basic georeferenced hydrographic data from the National Water and Sanitation Agency (ANA). With this study, a basin has a shape that is not very susceptible to natural floods or from anthropogenic changes in land use and cover. BRC deforestation values were estimated for random machine learning. From the series, the identification of possible data. Finally, the correlation between deforestation and the main hydroclimatic elements was the Pearson correlation. No significant trends were observed in the hydroclimatic data analysis in the analysis. However, a reduction (168%) was observed in the area of native vegetation between 19 and 2, with a significant increase from 2007 from the year 2007. and the hydroclimatic information of the basin. of possible protection, but of forest protection, it is still not possible to verify between forest protection and the main forest protection. This can be explained by the large territorial extension of the basin and the size of its deforested area.